The C-terminal domain of T4 RNA ligase 1 confers specificity for tRNA repair - Wang, Li Kai (Cold Spring Harbor Laboratory Press, 2007)
T4 RNA ligase 1 (Rnl1) is a tRNA repair enzyme that thwarts a tRNA-damaging host response to virus infection. The 374-aa Rnl1 protein consists of an N-terminal nucleotidyltransferase domain fused to a unique C-terminal domain composed of 10 α helices. We exploited an in vitro tRNA splicing system to demonstrate that Rnl1 has an inherent specificity for sealing tRNA with a break in the anticodon loop. The tRNA specificity is imparted by the C domain, any deletion of which caused the broken tRNA to be sealed as poorly as the linear intron in vitro and also abolished Rnl1 tRNA splicing activity in vivo. Deletion analysis demarcated Rnl1-(1–254) as a minimal catalytic domain of Rnl1, capable of all chemical steps of the nonspecific RNA ligation reaction. Alanine scanning of the N domain identified Ser103, Leu104, Lys117, and Ser118 as important for pRNA ligation in vitro and tRNA repair in vivo.